CLASSIFYING THE READABILITY LEVEL OF READING TEXT ON ENGLISH TEXTBOOK ENTITLED “PATHWAY TO ENGLISH” - Rahmi, Ulfa; Riza, Armilia; Yelliza, Yelliza (Universitas PGRI Sumatera Barat, 2022)
Reading was an activitythat could not be separated from teaching andlearning activities. It cause the textbook was one of source in learning. In this case, each reading texts had different difficulties, so it was important for teacehrs to chose appropriate text for students so they would comprehended the text. Based on the phenomenon, the researchers interested to conduct a study that aimed to classified the readability of reading text on English textbook entitled